Synthesis and conductivity of copper zinc tin selenide quaternary chalcogenide semiconductor - Leong, Yong Jian (2016)
There are several absorber layer have been developed for solar cell application such as CdTe, CIGS and CIGSe. However, due to its toxicity and low absorption issue, Zinc and Tin have been introduced to substitute the Indium and Galium to form a new absorber material which is CZTSe. Conductivity of the material is playing an important role in determining the transporting electron properties. Several methods such as pulsed laser ablation, magnetron sputtering and co-evaporation method have been chosen to synthesize CZTSe. In this study, Solvothermal method has been chosen to synthesize Copper Zinc Tin Selenide (Cu2ZnSnSe4 or CZTSe) due to few benefits such as able to produce crystalline phase, easily manipulate the size, simple equipment and affordable cost. Ethylenediamine (En) behaves as a good complexing agent in creating a step by step stage for the binary and ternary compounds to react and form quaternary compounds. The formation of CZTSe will favor in alkaline condition which is caused by En. The concentrations of CuCl2.2H2O, Zn(CH3COO)2∙(H2O)2 and SnCl4∙5H2O were varied separately in three experiments to observe the effect of the precursors towards the formation of CZTSe. X-ray diffraction (XRD) has been used to determine the phases and structure. X-ray fluorescence (XRF) has been used to identify the chemical composition. Raman spectroscopy has been used to confirm the formation of CZTSe phase. Field emission scanning electron microscopy (FESEM) has been used to study the morphology of the samples. Resistivity measurements with Van der Pauw configurations have been used to observe the electrical properties. The CZTSe peaks have been confirmed by XRD peak at 2θ = 27.2o, 45.1o, 53.3o, 65.5o and 72.3o and it is attributed to tetragonal crystal structure based on XRD ICSD database. Raman spectroscopy has been further investigated to verify the formation of CZTSe phase which shows the wavenumber at about 172cm-1, 195cm-1 and 233cm-1. The results obtained showed that the precursors’ concentrations play an important role in the samples morphology. The CuCl2.2H2O precursors showed the irregular grain size morphology. The Zn(CH3COO)2∙(H2O)2 precursors showed the irregular grain size and rod-like structure morphology. The SnCl4∙5H2O precursors showed the irregular grain size and small particles grow on the surface material. The stoichiometry of CZTSe was slowly changing and deviate from the ideal ratio which is 2:1:1:4 by substituting the atom position in the crystal structure. The CuCl2.2H2O precursors and Zn(CH3COO)2∙(H2O)2 precursors showed the increasing conductivity trend whereas the SnCl4∙5H2O showed the decreasing conductivity trend due to the formation of SnO2.